BIOMONITORING PENCEMARAN UDARA MENGGUNAKAN LUMUT DAUN (Bryopsida) - Siratul Aini; M. Zulhilmi; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Air pollution is an increasing environmental problem due to human activities, such as industry and transportation, which produce various hazardous pollutants. One method that can be used to monitor air quality is biomonitoring using living organisms, such as bryophytes (Bryopsida). This study aims to determine the role and working mechanism of bryophytes as bioindicators of air pollution. The method used is a literature review by examining various relevant national and international scientific references, then analyzed descriptively. The results of the study indicate that bryophytes have the ability to absorb and accumulate air pollutants such as heavy metals (Pb, Cd, Hg) and pollutant gases (SO₂ and NOx) directly through their entire body surface. In addition, bryophytes are also very sensitive to environmental changes, so changes in their condition and presence can reflect the level of air pollution. Thus, bryophytes can be used as effective, efficient, and accurate bioindicators in air quality monitoring.